Stress-induced VIPergic activation mediates microbiota/Th17cell-dependent depressive-like behaviors - Medina-Rodriguez, Eva M.; Han, Dongmei; Zeltzer, Shanie E.; Moraskie Alvarez-Tabío, Michael P.; O’Connor, Gregory; Daunert, Sylvia; Beurel, Eléonore (Brain, behavior, and immunity, 2025)
•VIPergic promotion of depressive-like behaviors is dependent on the microbiome.•VIPergic activation increases SFB and hippocampal Th17 cells.•VIPergic activation induces IL-17A-mediated increase of hippocampal microglia. Chronic stress often has deleterious effects leading to the development of psychiatric diseases. The gut-brain axis represents a novel avenue for stress research. The negative effects of stress on the gut physiology have been well-described, whereas the pathways whereby stress controls microbial composition to modulate behaviors remains mainly unknown. We discovered that vasoactive intestinal peptide (VIP) activation promoted stress-induced microbial changes leading to increased infiltration of T helper (Th) 17 cells and microglial activation in the hippocampus and depressive-like behaviors, uncovering a close crosstalk between intestinal VIPergic release and the gut microbiota during stress and providing a new interaction between the nervous system and the gut microbiome after stress. Neutralization of the signature cytokine of Th17 cells, interleukin (IL)-17A, was sufficient to block depressive-like behaviors, reduce neuronal VIPergic activation and microglia activation induced by VIPergic activation after stress, opening new potential therapeutic targets for depression.